Books before print - Kwakkel, Erik (ARC Humanities Press, 2018)
This beautifully illustrated book provides an accessible introduction to the medieval manuscript and what it can tell us about the world in which it was made and used. Books Before Print explores how manuscripts can act as a vibrant and versatile tool to understand the deep historical roots of human interaction with written information. It highlights extraordinary continuities between medieval book culture and modern-world communication, as witnessed in medieval pop-up books, posters, speech bubbles, book advertisements, and even sticky notes.
Title from publisher's bibliographic system (viewed on 08 Feb 2021)
Keywords: Einführung; Handschriftenkunde; Terminologie; Handschrift; Bucheinband; Beschreibstoff; Randbemerkung; Initiale; Schreibschule; Buchgestaltung; Buch; Typus; Verwendung; Gebrauchsspur